First report on Cydonia oblonga Miller anticancer potential: differential antiproliferative effect against human kidney and colon cancer cells - Carvalho, Márcia (2021)
The present study reports the phenolic profile and antiproliferative properties of quince (Cydonia oblonga Miller) leaf and fruit (pulp, peel, and seed) against human kidney and colon cancer cells. The phenolic profiles of quince methanolic extracts were determined by high-performance liquid chromatography (HPLC)/diode array detector (DAD). 5-O-Caffeoylquinic acid was always one of the two major phenolic compounds present in all extracts, except for seed. Our results revealed that quince leaf and fruit extracts exhibited distinctive antiproliferative activities. The extracts from quince leaf showed concentration-dependent growth inhibitory activity toward human colon cancer cells (IC(50) = 239.7 +/- 43.2 microg/mL), while no effect was observed in renal adenocarcinoma cells. Concerning the fruit, seed extracts exhibited no effect on colon cancer cell growth, whereas strong antiproliferative efficiency against renal cancer cells was observed for the highest concentration assayed (500 microg/mL). The antiproliferative activity of pulp and peel extracts was low or absent in the selected range of extract concentrations. This is the first report showing that C. oblonga may be useful as a cancer chemopreventive and/or chemotherapeutic agent.